Evaluasi Strategi Penjualan Pada Café Allya - Fadila Marsanda; Shelfi Amanda Putri; Mutiara Anisah; Niati Syafputri; Ramdani Bayu Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the factors that influence the success of cafe businesses in Padang City. The research method used is quantitative with multiple linear regression analysis techniques. The research results show that the factors that influence the success of cafe businesses in Padang City are business location, product quality, product price, promotions and customer service. The problems found when conducting this research were that the marketing strategy was still lacking, there were many competitors, and the condition of the café building was still inadequate. The solution to the problem is, increasing marketing through social media, the products produced must be more varied and of better quality and provide a delicious and unique taste so that they can satisfy customers and the business is able to compete in market share, decorating the place to make it look more unique and attractive so that customers feel at home relax in a comfortable room. This article was prepared by observation, collecting data in interviews, and documentation. The results of this research show that customer satisfaction depends on the products produced and the services provided by employees.